Consideration of lamination structural analysis in a multi-layered composite and failure analysis on wing design application - Basri, Ernnie Illyani; Hameed Sultan, Mohamed Thariq; Basri, Adi Azriff; Mustapha, Faizal (Multidisciplinary Digital Publishing Institute, 2021)
A finite element (FE) model is developed to study the structural performance on a composite wing of a UAV with a tubercle design at the leading edge of the wing. The experimental study of the designation of the composite at the wing skin is carried out to prove the simulation validity through material characteristics. In this paper, the numerical modeling for simulation is highlighted to correlate the process parameter setting of simulation replicating the actual experimental tests. The percentage difference was calculated to be 11.1% by tensile and 10.47% by flexural. The numerical work applied the study of FE analysis and developed a standardized numerical approach for structural optimization, known as FE-ACP simulation. The significant findings of deformation are obtained according to Schrenk's aerodynamic loading, while the prediction of failure mode of Tsai-Wu under interaction among stresses and strains was acquired at the seventh and eighth layer of both spars.